First off Label Endovascular Clinical Experience to Treat Diffuse Cerebral Venous Sinus Thrombosis Using the INARI FlowTriever System: Case Report - Bushnaq, Saif; Kareem, Samer Abdul; Liaw, Nicholas; Alenzi, Bader; Ahmed, Muhammad Khaleeq; Bushnaq, Merna; Zaidat, Osama O. (Frontiers in Neurology, 2021)
Anticoagulation with heparin is the current mainstay treatment for Cerebral Venous Sinus Thrombosis (CVST). Endovascular treatment is increasingly being used to treat patients with CVST who are non-responsive to anticoagulation. These more aggressive interventions include catheter-based local chemical thrombolysis, balloon angioplasty and mechanical thrombectomy with uncertain safety and efficacy. Here we describe the first reported clinical experience using the INARI FlowTriever system to treat a patient presented with focal weakness and found to have diffuse CVST.